RIEMANNIAN HYPERSURFACES WITH CONSTANT SCALAR CURVATURE IN A HESSIAN MANIFOLD OF CONSTANT CURVATURE - Yilmaz, Munevver Yildirim; Bektas, Mehmet; Ergaut, Mahmut (Int Electronic Journal Geometry, 2009)
We investigated hypersurfaces with constant scalar curvature in a Hessian manifold of constant curvature and obtained two theorems on hypersurfaces of Hessian manifolds with non-negative constant curvature.
Keywords: Hypersurface; scalar curvature; Hessian manifold